Potentials of synthetic biodegradable mulch for improved livelihoods on smallholder farmers: a systematic review - Ramadhani, Ahamed Mwarabu; Nassary, Eliakira Kisetu; Rwehumbiza, Filbert B.; Massawe, Boniface H. J.; Nchimbi-Msolla, Susan (Frontiers in Agronomy, 2024)
Plastic waste in agriculture, particularly from polyethylene mulch, poses significant environmental challenges. Synthetic biodegradable mulch has emerged as a sustainable alternative, derived from renewable resources such as thermoplastic starch, polylactic acid, polyhydroxyalkanoates, and copolyesters. This review explores the benefits of synthetic biodegradable mulch, its environmental impact, and the policy landscape to support its adoption. A review of existing literature was conducted, focusing on three aspects: (1) the performance of synthetic biodegradable mulch in crop production and pest control, (2) the environmental, socioeconomic, and climate resilience compared to polyethylene mulch, and (3) the institutional policies that promote synthetic biodegradable mulch adoption. The analysis considered comparative data on yield, pest management, and sustainability metrics. Synthetic biodegradable mulch performs similarly or better than polyethylene mulch in various agricultural practices. It enhances crop yield, quality, and weed suppression, acts as a physical barrier against pests and diseases, reduces chemical usage, and aids in water and nutrient management. Moreover, synthetic biodegradable mulch offers environmental benefits by reducing plastic waste, microplastic pollution, and greenhouse gas emissions, contributing to climate change mitigation. While synthetic biodegradable mulch provides numerous advantages, adoption faces challenges such as high initial costs, farmer preferences, and the regulatory framework. Effective institutional policies and increased consumer demand could drive wider adoption, offering potential for improved livelihoods among small farmers while promoting environmental sustainability.